2020
DOI: 10.1186/s13620-020-00177-9
|View full text |Cite
|
Sign up to set email alerts
|

Causes of stress and conflict in the veterinary professional workplace – a perspective from Poland

Abstract: Background The problems of burnout and the moral and ethical distress resulting from various kinds of conflict have been raised in the veterinary profession. However, their sources and inter-relationships have not been thoroughly recognized mainly due to the multidimensional nature of human interactions related to animal breeding, farming, welfare, prophylaxis and therapy. For the first time in Poland, an analysis of conflict and conflict-causing factors in veterinary practice has been conducted with the parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…For example, a 2021 survey by the British Veterinary Association revealed that 57% of veterinary staff felt intimidated by their clients’ behavior in the previous year, marking a 10% increase from 2019 [ 6 ]. This intimidation contributed to adverse mental stress, strained relationships with future clients, increased work pressure, and even career burnout [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, a 2021 survey by the British Veterinary Association revealed that 57% of veterinary staff felt intimidated by their clients’ behavior in the previous year, marking a 10% increase from 2019 [ 6 ]. This intimidation contributed to adverse mental stress, strained relationships with future clients, increased work pressure, and even career burnout [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A considerable body of research underscores the increased work stress experienced by veterinary professionals, primarily due to suboptimal communication [ 7 , 14 , 19 , 20 ]. Veterinarians frequently express discontent or agitation from medical disputes due to communication breakdowns with clients.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations